Robust Preamble-Based Timing Synchronization for OFDM Systems - Yun Liu; Fei Ji; Hua Yu; Dehuan Wan; Fangjiong Chen; Ling Yang (Journal of Computer Networks and Communications)
This study presents a novel preamble-based timing offset estimation method for orthogonal frequency division multiplexing (OFDM) systems. The proposed method is robust, immune to the carrier frequency offset (CFO), and independent of the structure of the preamble. The performance of the new method is demonstrated in terms of mean square error (MSE) obtained by simulation in multipath fading channels. The results indicate that the new method significantly improves timing performance in comparison with existing methods.